Challenges and Strategies in Place-Based Multi-Stakeholder Collaboration for Sustainability: Learning from Experiences in the Global South - Ayala-Orozco, Bárbara; Rosell, Julieta A.; Merçon, Juliana; Bueno, Isabel; Alatorre-Frenk, Gerardo; Langle-Flores, Alfonso; Lobato, Anaid (Sustainability, 2018)
Addressing complex environmental problems requires the collaboration of stakeholders with divergent perspectives, a goal that is challenged by diverse factors. Challenges hindering multi-stakeholder collaboration (MSC) for sustainability have previously been addressed in the context of transnational partnerships. However, less is known regarding how place-based MSC operates, especially in the context of the Global South. To contribute to addressing the factors that hinder place-based MSC for sustainability in the Global South, we analyzed 38 MSC projects spanning diverse ecological and social contexts across Mexico. In a series of participatory workshops, 128 stakeholders from academia, government, business, local communities, and civil society organizations discussed factors that hinder place-based MSC and co-constructed strategies to strengthen collaboration. Some challenges coincided with those identified in previous studies (e.g., divergent visions, inadequate project planning), whereas other concerns that have not been commonly regarded as important emerged as crucial obstacles for MSC. We discuss these challenges in the context of areas of limited statehood and point to the traditions of popular education and participatory action research as a source of valuable tools for place-based MSC. We identify strategies capable of addressing diverse challenges, a result that could aid prioritizing resource allocation to strengthen MSC.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; collaboration / colaboração

Navigating in the Midst of Uncertainties: Challenges in Disaster Risk Governance in Mozambique - Koivisto, Jenni (Karlstads universitet, 2018)
Disasters cause heavy losses for societies and may quickly erode any development efforts. Consequently, disaster risk reduction (DRR) is an integral part of development work that should be addressed at multiple levels. Global DRR frameworks, scholars and practitioners all advocate disaster risk governance (DRG) strategies that are multi-stakeholder, polycentric and multisectoral. While various substantive knowledge gaps and questions arising from multiple risks and the crosscutting nature of DRR have been relatively well addressed, uncertainties relating to multiple DRR actors operating and collaborating at different scales have gained less attention in previous studies. This thesis investigates the uncertainties in DRG in Mozambique, a low-income country that regularly faces natural hazards. These hazards often cause heavy loss of life and livelihoods and economic damage. The four articles that together constitute this thesis focus on different sets of uncertainties and factors that have constrained or allowed Mozambique to take major steps in this policy area. By exploring strategic and institutional uncertainties related to stakeholder involvement, coordination and policy disputes, this thesis reveals different challenges and opportunities that affect DRR policymaking in Mozambique. This thesis concludes that Mozambique has managed to take important steps in DRR. However, as a consequence of the different challenges to DRR practice in Mozambique, policymaking can be short-sighted and makes slow progress, thus increasing the disconnect between theory, policies and practice. This thesis thus argues that DRG research and practice need to better take into account power-relations; coordination and capacity issues; and responsibilities and transparency across scales, both in Mozambique and elsewhere.
Keywords: G - Mozambique / Moçambique; L - english / inglês; collaboration / colaboração